“YouTube” for Surgical Training and Education in Donor Nephrectomy: Friend or Foe? - Mohamed El-Mahrouk; Derar Jaradat; Tim Eichler; Robert Sucher; Christian Margreiter; Andri Lederer; Robert Karitnig; Antonia Geisler; Nora Jahn; Hans Michael Hau (Journal of Medical Education and Curricular Development)
Background The COVID-19 pandemic has accelerated the shift toward e-learning and online education in surgical training. With the increasing prevalence of end-stage chronic kidney disease, kidney transplantation is in high demand. Donor safety is crucial in nephrectomy procedures, highlighting the importance of effective training. This study evaluates the quality and effectiveness of YouTube videos focusing on laparoscopic and robotic donor nephrectomy for surgical education. Methods On October 24, 2023, searches on YouTube for “laparoscopic live donor nephrectomy” and “robotic live donor nephrectomy” returned 121 videos, with 63 included in the study. Popularity was evaluated using the Video Power Index (VPI), while reliability and quality were assessed using the LAP-VEGaS Video Assessment Tool and Journal of the American Medical Association (JAMA) benchmark criteria. Additionally, a structured descriptive tool called the “Live Donor Nephrectomy Completeness (LDNC)” was created to evaluate the completeness and educational value of procedural technical steps. Results Out of 63 videos reviewed, laparoscopic surgical procedures were depicted in 71.4% of them, while robotic approaches were shown in 28.6%. Academic backgrounds were associated with 54% of the videos, and individual physician backgrounds with 46%. Mean scores were LAP-VEGaS 9.79 ± 3.87, VPI 6.32 ± 3.31, and LDNC 9.68 ± 1.97. JAMA scores varied, with 34.9% receiving 1 point, 34.9% receiving 2 points, 17.5% receiving 3 points, and 12.7% receiving 4 points. Academic videos scored significantly higher in LAP-VEGaS and LDNC (all p  < .01). While LAP-VEGaS, VPI, and LDNC scores correlated significantly (all p  < .05), no correlation was found between JAMA score and other scoring systems. Videos with more clicks and likes showed significantly better scores across all measures (all p  < .05). Conclusion Amidst the challenges posed by the pandemic on surgical education, YouTube has emerged as a valuable resource for learning about laparoscopic and robotic donor nephrectomy for living kidney donation. However, the quality and reliability of these videos vary greatly, and many lack thorough reviews, leading to incomplete information. To enhance their educational value, it's proposed that videos undergo professional evaluation before publication and adhere to standardized, structured, and validated scoring systems, ensuring logical structure and improved quality.